Empowerment, partner’s behaviours and intimate partner physical violence among married women in Uganda - Kwagala, Betty; Ojiambo Wandera, Stephen; Ndugga, Patricia; Kabagenyi, Allen (BMC public health, 2013)
There is dearth of knowledge and research about the role of empowerment, partners’ behaviours and intimate partner physical violence (IPPV) among married women in Uganda. This paper examined the influence of women’s empowerment and partners’ behaviours on IPPV among married women in Uganda. Methods: The 2011 Uganda Demographic and Health Survey data were used, selecting a weighted sample of 1,307 women in union considered for the domestic violence module. Cross tabulations (chi-square tests) and multivariate logistic regressions were used to identify factors associated with IPPV. Results: The prevalence of IPPV among women in union in Uganda is still high (41%). Women’s occupation was the only measure of empowerment that was significantly associated with IPPV, where women in professional employment were less likely to experience IPPV. Women from wealthy households were less likely to experience IPPV. IPPV was more likely to be reported by women who had ever had children and witnessed parental IPPV. IPPV was also more likely to be reported by women whose husbands or partners: accused them of unfaithfulness, did not permit them to meet female friends, insisted on knowing their whereabouts and sometimes or often got drunk. Women who were afraid their partners were also more likely to report IPPV.
Keywords: Intimate partner violence; Decision-making; Alcohol; Controlling behaviours; Uganda